Syndromic craniosynostosis: neuropsycholinguistic abilities and imaging analysis of the central nervous system - Maximino, Luciana Paula; Ducati, Luis Gustavo [UNESP]; Marques Abramides, Dagma Venturini; Correa, Camila de Castro [UNESP]; Garcia, Patricia Fernandes; Fernandes, Adriano Yacubian [UNESP] (Assoc Arquivos Neuro- Psiquiatria, 2017)
Objective: To characterize patients with syndromic craniosynostosis with respect to their neuropsycholinguistic abilities and to present these findings together with the brain abnormalities. Methods: Eighteen patients with a diagnosis of syndromic craniosynostosis were studied. Eight patients had Apert syndrome and 10 had Crouzon syndrome. They were submitted to phonological evaluation, neuropsychological evaluation and magnetic resonance imaging of the brain. The phonological evaluation was done by behavioral observation of the language, the Peabody test, Token test and a school achievement test. The neuropsychological evaluation included the WISC III and WAIS tests. Results: Abnormalities in language abilities were observed and the school achievement test showed abnormalities in 66.67% of the patients. A normal intelligence quotient was observed in 39.3% of the patients, and congenital abnormalities of the central nervous system were observed in 46.4% of the patients. Conclusion: Abnormalities of language abilities were observed in the majority of patients with syndromic craniosynostosis, and low cognitive performance was also observed.
Keywords: acrocephalosyndactylia; craniofacial dysostosis; central nervous system; neuropsychology; language